2007
DOI: 10.1530/rep-07-0259
|View full text |Cite
|
Sign up to set email alerts
|

Release of phospholipase C ζand [Ca2+]i oscillation-inducing activity during mammalian fertilization

Abstract: During fertilization of mammalian eggs a factor from the sperm, the sperm factor (SF), is released into the ooplasm and induces persistent [Ca 2C ] i oscillations that are required for egg activation and embryo development. A sperm-specific phospholipase C (PLC), PLCz, is thought to be the SF. Here, we investigated whether the SF activity and PLCz are simultaneously and completely released into the ooplasm soon after sperm entry. To accomplish this, we enucleated sperm heads within 90 min of intracytoplasmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 68 publications
2
60
1
Order By: Relevance
“…It has previously been that PLCζ is localized in the perinuclear theca in the post-acrosomal region [27,28]. Our present study confirmed, for the first time, that rat PLCζ is also localized in the acrosomal region in sperm (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…It has previously been that PLCζ is localized in the perinuclear theca in the post-acrosomal region [27,28]. Our present study confirmed, for the first time, that rat PLCζ is also localized in the acrosomal region in sperm (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that PLCz is detectable in the post-acrosomal region (Yoon & Fissore 2007) and in the acrosomal and post-acrosomal regions ) of mouse sperm, in the acrosomal region of rat sperm (Seita et al 2009), in the equatorial , or equatorial and post-acrosomal regions (Heytens et al 2009) of human sperm, and in the equatorial region of bull sperm (Yoon & Fissore 2007). In mice, it is known that the components of the tail are not required for induction of oocyte activation (Kuretake et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro PLC assays, using recombinant PLCz confirmed the enzyme's high sensitivity to Ca 2þ , which render it nearly fully active at basal [Ca 2þ ] i concentrations ). Immunolocalization studies localized PLCz to the postacrosomal region of mouse sperm (Fujimoto et al 2004) and to the equatorial area of bull and human sperm (Yoon and Fissore 2007;Grasa et al 2008;Yoon et al 2008), regions that first come in contact with the ooplasm following gamete fusion, respectively (Sutovsky et al 2003).…”
Section: Identification Of Plczmentioning
confidence: 99%